Global regulatory policies for animal biotechnology: overview, opportunities and challenges - Wray-Cahen, Diane; Hallerman, Eric; Tizard, Mark (Frontiers in Genome Editing, 2024)
Genome editing (GnEd) has the potential to provide many benefits to animal agriculture, offering a means for achieving rapid growth, disease resistance, and novel phenotypes. The technology has the potential to be useful for rapidly incorporating traits into existing selectively bred animals without the need for crossbreeding and backcrossing. Yet only four products from animals created via biotechnology, all growth-enhanced fishes, have reached commercialization and only on a limited scale. The past failure of genetically engineered (or GM) products to reach conventional producers can largely be attributed to the high cost of meeting GMO regulatory requirements. We review the history of GMO regulations internationally, noting the influence of Codex Alimentarius on the development of many existing regulatory frameworks. We highlight new regulatory approaches for GnEd organisms, first developed by Argentina, and the adoption of similar approaches by other countries. Such new regulatory approaches allow GnEd organisms that could have been developed by conventional means to be regulated under the same rules as conventional organisms and in the future is likely to enhance the opportunity for biotech animals to enter production. Treating certain GnEd products as conventional has had a large impact on the variety of biotechnological innovations successfully navigating regulatory processes. We suggest that for the full potential of GnEd technologies to be realized, enabling public policies are needed to facilitate use of GnEd as a breeding tool to incorporate new traits within existing animal breeding programs, rather than only a tool to create distinct new products. Table 2. Global approaches to regulation of agricultural applications of precision biotechnology (genome editing). 1038 Category Defining Questions Categories of Products of Precision Breeding Techniques Null Segregant Could be obtained via "conventional crossbreeding" or via mutagenesis? yes yes yes no yes Nucleic acid template? no short long yes NA "Foreign" DNA (Synthetic or Transgenic) no no no yes NA * FAS GAIN: https://gain.fas.usda.gov/#/ (updated annually) Details on country policies available in the USDA GAIN system and in the weblinks below Weblinks to Country Policies: